Visible-Light-Driven Degradation of Chloramphenicol Using CeO2 Nanoparticles Prepared by a Supercritical CO2 Route: A Proof of Concept - Maria Chiara Iannaco; Antonietta Mancuso; Stefania Mottola; Andrea Pipolo; Vincenzo Vaiano; Iolanda De Marco (Nanomaterials)
Recently, the extensive use of antibiotics has unavoidably resulted in the discharge of significant quantities of these drugs into the environment, causing contamination and fostering antibiotic resistance. Among various approaches employed to tackle this problem, heterogeneous photocatalysis has emerged as a technique for antibiotic degradation. This study explores the potential of CeO2 as a photocatalyst for the degradation of chloramphenicol. Supercritical antisolvent (SAS) processing was successfully employed to synthesize photocatalyst precursor nanoparticles. After thermal annealing, the CeO2 samples were characterized through UV–Vis diffuse reflectance spectroscopy to evaluate the band gap energy values. Raman and FT-IR spectroscopy confirmed the presence of oxygen vacancies in the CeO2 lattice. During photocatalytic experiments, the CeO2 derived from the SAS-processed precursor exhibited superior photocatalytic performance compared to the catalyst synthesized from the non-micronized precursor. Various annealing temperatures were employed to tune the oxygen vacancy of CeO2. Furthermore, the impact of catalyst dosage and chloramphenicol concentration was investigated. Under optimal reaction conditions (25 mg L−1 chloramphenicol and 2.25 g L−1 catalyst dosage), a degradation efficiency of 64% was achieved. Finally, to elucidate the degradation mechanism, different scavengers (EDTA, benzoquinone, and isopropyl alcohol) were utilized, revealing that the superoxide radical is the primary species responsible for chloramphenicol degradation.